Prescription drug abuse : a reference handbook - Newton, David E. (Santa Barbara, California : ABC-CLIO, LLC ; an imprint of ABC-CLIO, LLC, 2016)
"This outstanding resource guide for students and young adults provides an introduction to the history of prescription drug abuse that explains how this problem has arisen and examines the social, political, economic, and health issues associated with prescription drug abuse in modern society. Evidence suggests that both adults and youth are abusing a wider range of prescription drugs and abusing them more frequently than has been the case in the past. Prescription drugs are the second most common class of drugs abused by Americans, more than twice as commonly abused as cocaine, and five times as commonly abused as heroin. This book provides readers with information about the specific health effects that can result from using certain types of medical chemicals, particularly opioid analgesics, stimulants, depressants, and hallucinogenics; explains the most important factors that have led to the growth of prescription drug problems; and reviews the current status of the issue in the United States and other nations. Readers will learn about the dangers associated with the use of prescription drugs for nonmedical purposes, the methods that have been put in place and are being developed to prevent the abuse of prescription drugs, and the trends in prescription drug misuse, with possible explanations for these trends. The book also reviews some of the steps being taken by governments and other organizations and agencies to combat the problem of prescription drug abuse"--Publisher's description.
Background and history -- Problems, controversies, and solutions -- Perspectives -- Profiles -- Data and documents -- Resources -- Chronology.
Includes bibliographical references and index.
Keywords: Drug abuse; Medication abuse